(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Plastics are important resources in the circular economy, and the best way to manage them sustainably is to recycle them after their useful lives with minimal environmental harm and the generation of economic value. The initiative clarifies how plastic is used in civil construction.. The component used include everything from plastic screws and hanger to bigger plastic parts that are used in decoration, electric wiring, flooring, wall covering and water proofing. There has been a considerable imbalance between the availability of conventional building materials and their demand in the recent past. On the other hand, laterite quarry debris is widely available, and disposing of waste plastics (PET, PP, etc.) is the biggest difficulty because only a small percentage of PET bottles are recycled and because continuous recycling of PET bottles could result in it becoming a carcinogenic material. In order to meet the rising need for traditional construction materials, the manufactured bricks have qualities like smooth and even finishing, minimal water absorption, and adequate compressive strength as compared to laterite stone.